The U.S. Foreign Policy under Trump Administration to Recognize Jerusalem as the State Capital of Israel - Aswar, Hasbi (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2018)
A speech from the President of United States, Donald Trump, who explicitly state Jerusalem as the capital city of Israel triggering debate that threatens harmonization of the Middle East. Disagreement appear from South East Asia state up to European state regarding to Trump’s statement, which turn into United States foreign policy. Trump’s statement described as the main reason of increasing tension Palestinian – Israel conflict. This essay argues that The US policy toward Jerusalem was merely influenced by domestic politics in the sense that to satisfy Trump`s main voters of the Republican Party that is Evangelical Christian base.